ASTROPHYSICAL S-FACTOR OF 6Li(p,γ)7Be REACTION FROM EXPERIMENTAL DATA USING DIFFERENT METHODS - Burtebayev, N.; Amar, A.; Dubovichenko, S.B.; Sakuta, S.B.; Artemov, S.V.; Kerimkulov, Zh. (Recent Contributions to Physics, 2011)
New measurements of the 6Li(p,γ)7Be reaction γ-ray angular distributions have been done at beam energies of Ep, lab. = 387, 690, 984 and 1283 keV for the γ-ray transitions to the ground and first excited (1/2-, 429 keV) states in 7Be. Our calculations of the cross section of the 6Li (p, γ)7Be reaction was carried within the framework of the direct capture in the potential model using Fresco program. We extracted both of spectroscopic factors of 7Be and astro S-factor 6Li+p→7Be+γ from experimental data using two different methods.
Keywords: potential model; Fresco program; 6Li(p,γ)7Be reaction